Solve using the Square Root Property 8x^2+10x-7=0

Math
8×2+10x-7=0
Factor by grouping.
Tap for more steps…
For a polynomial of the form ax2+bx+c, rewrite the middle term as a sum of two terms whose product is a⋅c=8⋅-7=-56 and whose sum is b=10.
Tap for more steps…
Factor 10 out of 10x.
8×2+10(x)-7=0
Rewrite 10 as -4 plus 14
8×2+(-4+14)x-7=0
Apply the distributive property.
8×2-4x+14x-7=0
8×2-4x+14x-7=0
Factor out the greatest common factor from each group.
Tap for more steps…
Group the first two terms and the last two terms.
(8×2-4x)+14x-7=0
Factor out the greatest common factor (GCF) from each group.
4x(2x-1)+7(2x-1)=0
4x(2x-1)+7(2x-1)=0
Factor the polynomial by factoring out the greatest common factor, 2x-1.
(2x-1)(4x+7)=0
(2x-1)(4x+7)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
2x-1=0
4x+7=0
Set the first factor equal to 0 and solve.
Tap for more steps…
Set the first factor equal to 0.
2x-1=0
Add 1 to both sides of the equation.
2x=1
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2x=1 by 2.
2×2=12
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2×2=12
Divide x by 1.
x=12
x=12
x=12
x=12
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
4x+7=0
Subtract 7 from both sides of the equation.
4x=-7
Divide each term by 4 and simplify.
Tap for more steps…
Divide each term in 4x=-7 by 4.
4×4=-74
Cancel the common factor of 4.
Tap for more steps…
Cancel the common factor.
4×4=-74
Divide x by 1.
x=-74
x=-74
Move the negative in front of the fraction.
x=-74
x=-74
x=-74
The final solution is all the values that make (2x-1)(4x+7)=0 true.
x=12,-74
Solve using the Square Root Property 8x^2+10x-7=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top